2014
DOI: 10.1044/2014_jslhr-h-12-0323
|View full text |Cite
|
Sign up to set email alerts
|

Do Adults With Cochlear Implants Rely on Different Acoustic Cues for Phoneme Perception Than Adults With Normal Hearing?

Abstract: Purpose Several acoustic cues specify any single phonemic contrast. Nonetheless, adult, native speakers of a language share weighting strategies, showing preferential attention to some properties over others. Cochlear implant (CI) signal processing disrupts the salience of some cues: in general, amplitude structure remains readily available, but spectral structure less so. This study asked how well speech recognition is supported if CI users shift attention to salient cues not weighted strongly by native speak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 55 publications
6
60
0
Order By: Relevance
“…Previous phonetic cue-weighting studies with CI listeners suggest that limitations in the use of preferred acoustic cues can be complemented by increases in the use of secondary cues (Winn et al, 2012;Moberly et al, 2014), and the current study suggests that this phenomenon has implications for word recognition in general. CI listeners in this study who showed a cue-weighting pattern most similar to NH listeners in the unprocessed condition also tended to show best word recognition.…”
Section: Discussionmentioning
confidence: 79%
“…Previous phonetic cue-weighting studies with CI listeners suggest that limitations in the use of preferred acoustic cues can be complemented by increases in the use of secondary cues (Winn et al, 2012;Moberly et al, 2014), and the current study suggests that this phenomenon has implications for word recognition in general. CI listeners in this study who showed a cue-weighting pattern most similar to NH listeners in the unprocessed condition also tended to show best word recognition.…”
Section: Discussionmentioning
confidence: 79%
“…However, they did find that the CI users that utilized formant transition perceptual weighting strategies most similar to NH listeners when categorizing the /ba/-/da/ contrast exhibited the best word recognition scores. Similarly, Moberly et al (2014) documented that CI users that utilized perceptual weighting strategies most similar to NH listeners when categorizing the /ba/-/wa/ contrast exhibited superior word recognition performance as well. It is possible that the listeners in our study that exhibited the greatest training-related gains were using a different perceptual listening strategy to categorize the speech sounds than the CI users that showed only small behavioral changes.…”
Section: Success and Limitations Of Trainingmentioning
confidence: 94%
“…All measures were prerecorded to maintain consistent presentation levels and presented at 68 dB SPL. Spoken word recognition was measured using a Central Institute for the Deaf Word List (CID-W22) of 50 words, selected because previous work has demonstrated a wide range of variability in CI users when tested in quiet (21,22). Recognition of spoken words in meaningful sentences was tested using the Institute of Electrical and Electronics Engineers (IEEE) corpus (23), chosen because these 25 sentences are more complex than most clinical batteries (e.g., AzBio or HINT), and a wide range of performance has been demonstrated among adult CI users.…”
Section: Methodsmentioning
confidence: 99%